Главная

Алгебра 7 класс Ю.Н. Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

ГДЗ учебник по алгебрее 7 класс Ю.Н. Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г.

Раздел:

Номер №595

Упростите выражение:
а)
$(a^2 - 0,45a + 1,2) + (0,8a^2 - 1,2a) - (1,6a^2 - 2a)$
;
б)
$(y^2 - 1,75 - 3,2) - (0,3^2 + 4) - (2y - 7,2)$
;
в)
$6xy - 2x^2 - (3xy + 4x^2 + 1) - (-xy - 2x^2 - 1)$
;
г)
$-(2ab^2 - ab + b) + 3ab^2 - 4b - (5ab - ab^2)$
.

Решение а

$(a^2 - 0,45a + 1,2) + (0,8a^2 - 1,2a) - (1,6a^2 - 2a) = a^2 - 0,45a + 1,2 + 0,8a^2 - 1,2a - 1,6a^2 + 2a = 0,2a^2 + 0,35a + 1,2$

Решение б

$(y^2 - 1,75 - 3,2) - (0,3^2 + 4) - (2y - 7,2) = y^2 - 1,75y - 3,2 - 0,3y^2 - 4 - 2y + 7,2 = 0,7y^2 - 3,75y$

Решение в

$6xy - 2x^2 - (3xy + 4x^2 + 1) - (-xy - 2x^2 - 1) = 6xy - 2x^2 - 3xy - 4x^2 - 1 + xy + 2x^2 + 1 = -4x^2 + 4xy$

Решение г

$-(2ab^2 - ab + b) + 3ab^2 - 4b - (5ab - ab^2) = -2ab^2 + ab - b + 3ab^2 - 4b - 5ab + ab^2 = 2ab^2 - 4ab - 5b$